Evaluation of advanced sorghum (Sorghum bicolor L. Moench) hybrid genotypes for grain yield in moisture stressed areas of Ethiopia - Temesgen Teressa; Tamirat Bejiga; Zigale Semahegn; Amare Seyoum; Hailegebriel Kinfe; Amare Nega; Ligaba Ayele; Daniel Nadew; Mohammed Salah; Sewmehon Siraw; Mesfin Bekele; Solomon Mitiku; et al. (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Sixty two advanced hybrid sorghum varieties were evaluated in three environments, Kobo (KB), Sheraro (SH) and Mieso (MS) during 2019 of the main season. The objective of this study was to evaluate sorghum hybrids for production in drought stressed areas of Ethiopia. The experiment was piloted using a randomized complete block design with two replications. The result of over sites showed for grain yield, environments, environment by block and genotype by environment interaction effect highly significant variability among the genotypes. These point out that the variability among varieties and highly diverse growing situations across these three environments and vital in governing the expression of these traits. Significant genotype interaction by environment resulted either from differential responses of the variety or the test environments were highly significant (P ≤ 0.001). Out of 62 genotypes, G52, G47 and G38 were with near zero IPCA scores and hence have less interaction with the environments. Out of which only G47 and G52 had above average yield performance. Among environments, SH exhibited near zero IPCA1 score and hence had small interaction effects among environments, indicating that all the genotypes performed well in this location. So, it is the most favorable environments for most genotypes while MS and KB were good for only few genotypes. Genotypes, G36, G49, G37, G12, G68 and G6 generally exhibited high yield of positive IPCA1 score, from which G28, G55 and G34 had high IPCA1 scores in which G55 and G28 being the overall best genotype. Hence, the G55 and G28 were identified as specially adapted and the highest yielding genotype to the corresponding environments. Generally, G33 can be recommended for specific adaptation whereas, G55 and G28 relatively for wider adaptation.